Spatial and temporal distribution of tributyltin in the coastal environment of the Croatian Adriatic (2016-2023): TBT remains a cause for concern - Furdek Turk, Martina; Vrana, Ivna; Milačič, Radmila; Ščančar, Janez; Dautović, Jelena; Ciglenečki, Irena; Mikac, Nevenka (Frontiers in Marine Science, 2024)
This work presents a spatial and temporal trend distribution of tributyltin (TBT) and TBT pollution assessment along of the Croatian Adriatic coast in the period 2016 -2023. The monitoring of TBT pollution was carried out within the Water Framework Directive (2000/60/EC) and the Marine Strategy Framework Directive (2008/56/EC). TBT concentrations were measured at 63 sites in coastal and transitional waters in three compartments -water, sediments and mussels. The ranges of TBT concentrations were <0.06 -6.40 ng(TBT)/L in the water column, <1 -2546 ng(TBT)/g(d.w.) in sediments, and <1 -655 ng(TBT)/g(d.w.) in mussels, with while transitional waters being were in general more polluted than coastal waters. Monitoring of TBT concentrations in water showed that 30% of monitored sites were continuously polluted with TBT, with average annual concentrations exceeding AA-EQS (0.2 ng(TBT)/L), while 20% of the sites had concentrations in sediments above the proposed EQS for sediments (1.6 ng(TBT)/g(d.w.)). In mussels, TBT was detected at 70% of the sites with more than 60% of the sites exceeding the OSPAR criteria (12.6 ng(TBT)/g(d.w.)), indicating that the occurrence of imposex in gastropods at these sites is very likely. Only a slight decrease in TBT levels was observed over the investigated period, while but concentrations at most contaminated sites did not fall below the EQS. In summary, tThis study shows that, despite the ban of TBT-based antifouling paints more than 15 years ago (except for public and military vessels), contamination of the Croatian Adriatic coast with TBT still exists and regular monitoring is essential. The TBT distribution was primarily determined by the vicinity of the pollution source, i.e. shipping traffic, but the role of physicochemical parameters, such as dissolved organic carbon (DOC) and transparency of the water column, should not be disregarded, as well as the influence of hydrodynamics in the transitional waters. Although monitoring of TBT concentrations in water is an established approach to assess recent pollution, this long-term study has shown that mussels can be the most reliable indicator of pollution in a given area over the last several months.